Bacterial RNA Polymerase-DNA Interaction—The Driving Force of Gene Expression and the Target for Drug Action - Lee, Jookyung; Borukhov, Sergei (Frontiers in Molecular Biosciences, 2016)
DNA-dependent multisubunit RNA polymerase (RNAP) is the key enzyme of gene expression and a target of regulation in all kingdoms of life. It is a complex multifunctional molecular machine which, unlike other DNA-binding proteins, engages in extensive and dynamic interactions (both specific and nonspecific) with DNA, and maintains them over a distance. These interactions are controlled by DNA sequences, DNA topology, and a host of regulatory factors. Here, we summarize key recent structural and biochemical studies that elucidate the fine details of RNAP-DNA interactions during initiation. The findings of these studies help unravel the molecular mechanisms of promoter recognition and open complex formation, initiation of transcript synthesis and promoter escape. We also discuss most current advances in the studies of drugs that specifically target RNAP-DNA interactions during transcription initiation and elongation.